Preterm Birth in the United States A Sociocultural Approach - Bronstein, Janet M. (Springer International Publishing : Imprint: Springer, 2016)
This first-of-its-kind volume addresses the myriad of issues relating to-and reviews the plethora of responses to--premature births in the United States, both in national context and compared with other countries. In addition to current clinical data, it examines how preterm births in the U.S. fit in with larger social concerns regarding poverty, racial disparities, reproductive rights, gender expectations, and the business of health care. Comparisons with preterm birth phenomena in Canada, the U.K., and other Western European countries illustrate cultural narratives about motherhood, women's status, differences across social welfare and abortion policies , and across health care financing and delivery sytems, and how these may affect outcomes for newborns. The book sorts out these intersecting complexities through the following critical lenses:   ·         Clinical: causes, treatments, and outcomes of preterm birth ·         Population: the distribution of preterm births ·         Cultural: how we understand preterm birth       ·         Health care: delivering care for high-risk pregnant women and preterm infants ·         Ethical: moral decision-making about preterm births   Preterm Birth in the United States synthesizes a wide knowledge base for maternal and child health professionals across diverse disciplines, including public health, social work, nursing, medicine, and health policy. Social scientists with interests in reproduction and gender issues will gain access to historical, clinical and epidemiological knowledge that can support their work.  There is also an audience for the book among childbirth activists such as supporters of midwifery and less medicalized childbirth.                   .